ANALISIS YURIDIS PASAL 5C UU NO. 17 TAHUN 2022 PADA MASYARAKAT SUMATERA BARAT DALAM PERSPEKTIF SIYASAH QUR’ANIYAH - M. Doni; Muhammad Taufiq (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The birth of Law No.17 of 2022 concerning the Province of West Sumatra is considered to discriminate against one of the regions and ethnicities that exist in one administrative area of West Sumatra. Where in the Law there is article 5c which reads ‘West Sumatra Province has characteristics, namely Minangkabau customs and culture based on the philosophical values, Adaik basandi syara’ syara‘ bansandi kitabullah in accordance with the applicable Salingka Nagari customary rules, as well as historical wealth, language, arts, traditional villages / villages, rituals, traditional ceremonies, cultural sites, and local wisdom that show the religious character and height of the customs of the people of West Sumatra’ which is considered to discriminate against the Mentawai people. This research is alibrary research with data sources coming from primary sources collected from Law No.17 of 2022 and books related to the research along with secondary data obtained from intermediary media such as journals, news and the internet. After the data is obtained, it is analysed using qualitative analysis method. The results showed that the background of the problem related to Law No.17 of 2022 concerning West Sumatra Province article 5c which is considered to discriminate against the Mentawai people, because there are still pros and cons in the implementation process, such as the vagueness of some terms in the regulation, the lack of facilities and infrastructure and the lack of public knowledge about this regulation. In the view of fiqh siyasah, the formation of this legislation by the Government as the holder of power or ahlu al-halli wa al- aqdi is to maintain the benefit of the people.